Association of D-dimer levels with all-cause mortality in a healthy adult population: findings from the MOLI-SANI study - Augusto Di Castelnuovo; Amalia de Curtis; Simona Costanzo; Mariarosaria Persichillo; Marco Olivieri; Francesco Zito; Maria Benedetta Donati; Giovanni de Gaetano; Licia Iacoviello (Haematologica, 2013)
Elevated D-dimer levels are reportedly associated with higher risk of total mortality in patients with different diseases. We investigated whether a similar association could be found in a large, apparently healthy population. A large sample of individuals (N=17,359, 47% men, age ≥35 years) free of clinically recognized cardiovascular and cancer disease, for whom baseline D-dimer level was available, were studied within the MOLI-SANI cohort, randomly recruited from the general adult population of Southern Italy. The cohort was followed for a median of 4.2 years (73,807 person-years). D-dimer was measured in fresh citrated plasma by an automated latex-enhanced immunoassay. Hazard ratios were calculated using three Cox-proportional hazard models. Two hundred and eighty deaths were recorded. When modeled as a continuous variable, D-dimer level at baseline showed a non-linear association with mortality, whose incidence increased only in the upper quartile of the distribution (D-dimer ≥221 ng/mL). Thus, the group of individuals with D-dimer